2017
DOI: 10.18805/ijare.v51i04.8428
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of flowering in acid lime (Citrus aurantifolia Swingle)

Abstract: India is the largest producer of acid lime in the world and they are used as fresh fruit or for the preparation of pickles and beverages. They are rich in vitamin C, minerals and salts. The seasonality of production leads to market glut which results in poor returns to the farmers. Hence, an experiment was conducted to manipulate and regulate flowering by using various plant growth regulators viz., GA­3 and cycocel, chemicals viz., KNO3 and salicylic acid at 11 different treatment combinations. The experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Harvest season started by September 17 and 23 in the 2020 and 2021 seasons (≈154 and 161 days from full bloom), respectively, when fruit reached the horticultural maturity (light green color stage and total acidity [TA] = 8 ± 0.16%) per the consumer preference [76,77]. Fruit yield was recorded as total weight (kg) and number of fruit per tree.…”
Section: Yield and Fruit Characteristicsmentioning
confidence: 99%
“…Harvest season started by September 17 and 23 in the 2020 and 2021 seasons (≈154 and 161 days from full bloom), respectively, when fruit reached the horticultural maturity (light green color stage and total acidity [TA] = 8 ± 0.16%) per the consumer preference [76,77]. Fruit yield was recorded as total weight (kg) and number of fruit per tree.…”
Section: Yield and Fruit Characteristicsmentioning
confidence: 99%
“…Mahalle et al,(2010) reported that two sprays of cycocel @ l000 ppm at an interval of one month before initiation of flowering in August and September for Hasta bahar flowering (i.e., September and October) of acid lime resulted in maximum yield in terms of number of fruits per tree and weight of fruits per tree and this treatment also improved the fruit quality in respect to juice %, TSS, acidity, ascorbic acid content, peel and pomace per centage. Prabhu et al, (2017) reported maximum initial fruit set, fruit retention, number of fruit/ tree, fruit weight and fruit yield in summer season acid lime cv. PKM 1 with spraying of GA 3 50 ppm in June + Cycoce"l 1000 ppm in September + Spraying of 2 % KNO 3 in October.…”
Section: Use Of Growth Regulatorsmentioning
confidence: 99%
“…Kagzi lime is used in almost every home of the Indian sub-continent to flavour food or in the preparation of pickles. India occupies the fifth position among major lime and lemon producing countries in the world and is the largest producer of acid lime [1]. In India, lime and lemon cover an area of 259 thousand hectares with a production of 2789 thousand MT [2].…”
Section: Introductionmentioning
confidence: 99%
“…The recalcitrant seeds impose serious storage problems due to their desiccation and chilling sensitivity. That soaking seeds in water for 12-36 hrs induces early germination, increases germination percentage and promotes growth has been demonstrated in kagzi lime [4], mango [1], jackfruit [5], aonla [6] and tamarind [7]. An experiment was therefore framed to study the effect of storage treatments, gibberellic acid and duration of soaking on seed germination and seedling growth in Kagzi lime.…”
Section: Introductionmentioning
confidence: 99%